Specificity analysis of anti-gliadin mouse monoclonal antibodies used for detection of gliadin in food for gluten-free diet - Sánchez, Daniel; Tucková, Ludmila; Burkhard, Martin; Plicka, Jan; Mothes, Thomas; Hoffmanová, Iva; Tlaskalová-Hogenová, Helena (Journal of agricultural and food chemistry, 2007)
A gluten-free diet (GFD) is the sole effective long-lasting treatment of celiac disease. Four monoclonal antibodies (Abs) were prepared by immunization of animals kept on GFD with gliadin. The specificity of these Abs to decapeptides of alpha- and gamma-gliadin and omega-secalin was analyzed by the PEPSCAN technique. Repetitive sequences of alpha- and gamma-gliadin and omega-secalin containing the motifs QPFPXQ (X = Q, L, P) were recognized by all Abs tested. These Abs also frequently reacted with peptides containing the sequences QQSFPQQ, QQTFPQP, and QPFRPQ. On the basis of PEPSCAN results two Abs--8D4 and 7C6--were selected for the construction of a new ELISA kit for the detection of gliadin in food. The comparison of data obtained using the newly developed ELISA kit and commercially available ones indicated that Abs selection on the basis of their fine specificity to gliadin is useful for sensitive detection of gliadin in foods.
Keywords: Animals; Enzyme-Linked Immunosorbent Assay; gluteny; Gliadin; sekvence aminokyselin; Antibodies, Monoclonal; Food Analysis; Mice; Amino Acid Sequence; myši; ELISA; analýza potravin; Antibody Specificity; Celiac Disease; Glutens; monoklonální protilátky; specificita protilátek; zvířata; gliadin; celiakie